Comparative Research on Total Transfer Capability Calculation using Load Model - Guoping Shi; Jun Liang; Peng Gu (Institute of Advanced Engineering and Science, 2013)
This paper proposes a method calculating total transfer capability(TTC) and critical voltage using static power model based on real-time recording data, traditional power system dispatching calculation doesn’t consider load model, which does not agree with the real, this paper compares TTC and critical voltage under different load model and P-V curves, on which load model has a strong influence, so load modeling is necessary based on real-time data and is significant for improving system stability. The simulations show necessity and suitability of the method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2330